The opportunistic pathogen Pseudomonas aeruginosa carries a secretable arachidonate 15-lipoxygenase - Vance, Russell E. (National Academy of Sciences, 2004)
In mammals, lipoxygenases play key roles in inflammation by initiating the transformation of arachidonic acid into potent bioactive lipid mediators such as leukotrienes and lipoxins. In general, most bacteria are believed to lack lipoxygenases and their polyunsaturated fatty acid substrates. It is therefore of interest that an ORF (PA1169) with high homology to eukaryotic lipoxygenases was discovered by analysis of the whole-genome sequence of the opportunistic bacterial pathogen Pseudomonas aeruginosa. Using TLC and liquid chromatography-UV-tandem mass spectrometry (LC-UV-MS-MS), we demonstrate that PA1169 encodes a bacterial lipoxygenase (LoxA) that converts arachidonic acid into 15-hydroxyeicosatetraenoic acid (15-HETE). Although mammalian lipoxygenases are cytoplasmic enzymes, P. aeruginosa LoxA activity is secreted. Taken together, these results suggest a mechanism by which a pathogen-secreted lipoxygenase may modulate host defense and inflammation via alteration of the biosynthesis of local chemical mediators.